Unveiling the impacts of climate change and human activities on land-use evolution in ecologically fragile urbanizing areas: a case study of China's Central Plains Urban Agglomeration - Jiang, Zhimeng; Li, Yan; Wu, Hao; Mohamed Shariff, Abdul Rashid; Zhou, Han; Fan, Kaixuan (Elsevier B.V., 2024)
Environmental changes driven by climate change and human activities have significantly influenced the spatiotemporal evolution of land–use in urbanizing, ecologically fragile areas. However, these dynamics remain inadequately explored in terms of their evolution over space and time. In this study, we used a combination of CA-Markov and Coupling coordinated models to analyze the impacts of climate change and human activities on land–use evolution in China's Central Plains Urban Agglomeration (CPUA) from 2000 to 2060. Our results reveal that environmental changes significantly influence the spatiotemporal evolution of land use, accelerating rural-to-urban conversions in ecologically vulnerable regions, as validated by a CA-Markov model Kappa coefficient of 0.8378. These impacts, however, are predicted to diminish over time, with the strongest effects observed in areas with high ecological fragility. Specifically, increasing variability in climate conditions and intensifying human activities have resulted in cropland reduction at a rate of −260 km2/year and a simultaneous increase in built-up areas at a rate of 200 km2/year. This study underscores the critical influence of environmental changes on land–use dynamics and provides insights for policymakers and planners on promoting ecological resilience and sustainable land–use management to tackle the evolving challenges of climate change and human-induced disturbances.